Wandering Spleen as a Cause of Acute Abdomen: A Surgical Conundrum from Acute Appendicitis to Splenic Torsion and Ischemic Small Bowel Volvulus - Fatimah Najid; Sanjeev Sandrasecra; Mohd Zuki Asyraf; Chang, Haur Lee; Firdaus Hayati; Nornazirah Azizan; Andee Dzulkarnaen Zakaria (2020)
Wandering spleen is renowned as a surgical enigma due to its diverse presentations. Due to lack of its attaching ligaments which would usually place it at the left hypochondrium region, the spleen ‘wanders’ and may be located anywhere within the abdominal cavity. This condition has been associated with many complications such as splenic torsion, pancreatitis and portal hypertension. We report a case of a wandering spleen presenting as acute appendicitis in an 18-year-old young active sportsman. The patient developed post-operative ileus and later intestinal obstruction which necessitated exploratory laparatomy onto which the final diagnosis of splenic and small bowel infarct due to splenic torsion with small bowel volvulus was made. Splenectomy, small bowel resection and primary anastomosis were performed and the patient made a full recovery.